The monetary system during the Mamluk period (872-922A.H. / 1468-1517A.D.) - Wan Kamal Mujani, (Penerbit Universiti Kebangsaan Malaysia, 2006)
The purpose of this article is to discuss the situation of the monetary system and the factors which affected its stability during the fifty years before the fall of the Mamluk kingdom in 922A.H./1517A.D. The discussions are based on the textual sources, numismatic evidence and modern analysis. In order to explore the issue comprehensively, the article begins with discussing the monetary situation before 872A.H./1468A.D. This is followed by an account of the situation of the monetary system during the period under review and finally, an analysis of the factors that affected the monetary system. The article reveals that the monetary systems during the period under consideration were frequently in an unstable situation. Numismatic evidence attests to the fact that the rulers reduced the weight of coins and their fineness and manipulated the exchange rates. One of the main reasons for this was the increasing financial needs of the government which had to cover various expenses including some for their own personal benefits. Another reason which affected the monetary system during that time was the adulteration of the coinage